Glossary of psychological instruments: definition of 14 most used instruments in psychology - Pereyra Quiñones, José Luis (2021)
Tests, scales and inventories are useful tools in psychology since they are used to make precise measurements and every year the vademecum of psychometric and projective instruments increases. An international website has managed to count 5247 instrument titles; that is, these tools have increased arithmetically. Having more tools is advantageous, but the new psychometric writers or test authors present so many singularities and inaccuracies in the description of their respective instruments, which make it necessary to have a glossary, a more precise dictionary that defines the fourteen most used instruments in psychology clinical, educational and organizational (Pereyra, 2020).